High Densities of a Prochlorophyte (Unresolved Species) Inhibit Grazing by the Herbivorous Copepod Parvocalanus crassirostris - Ma, Xiao; Jacoby, Charles A.; Johnson, Kevin B. (Frontiers in Marine Science, 2021)
Harmful algal blooms (HABs) are increasing in frequency and severity, underscoring the importance of understanding potential top-down controls of blooms. In the Indian River Lagoon (IRL), a shallow subtropical estuary, one harmful bloom was co-dominated by an unresolved prochlorophyte in the Family Prochlorothricaceae, which reached densities of > 106 cells ml–1 engendering the term “Superbloom.” Experiments were conducted to evaluate grazing rates and the potential for top-down control by an abundant herbivorous copepod, Parvocalanus crassirostris, on the prochlorophyte. Those grazing rates were lower than the rates on a palatable alternative algal food, Isochrysis galbana, when both algal species were presented in monocultures with identical densities. Grazing on the prochlorophyte decreased or ceased at densities over 4.8 × 105 cells ml–1. When the prochlorophyte and the palatable alternative each comprised half of the total density, both species were consumed, but grazing on I. galbana was reduced compared to the grazing rates in a monoculture of this species, especially at higher cell densities. Copepod mortality was observed in treatments with high concentrations of the prochlorophyte, and these treatments contained mucilage. Experiments simulating viscosities produced by prochlorophyte mucilage yielded results consistent with the original grazing experiments (i.e., copepods showed lower grazing rates and higher mortality rates in higher viscosity treatments). Results reveal potential limitations of top-down controls by this grazer on prochlorophyte blooms and HABs that produce mucilage.